Analisis Manajemen Piutang Untuk Meminimalkan Risiko Piutang Tak Tertagih Pada Organisasi INKINDO Sumatera Barat - Anggraeni, Milla Rizky; Sudiman, Josephine; Herman, Lisa Amelia (Akuntansi dan Manajemen, 2023)
The Indonesian Consultants National Association (INKINDO) is one of the associations of consulting services companies in Indonesia. In carrying out organizational activities, INKINDO West Sumatra requires members to pay membership dues every year which results in bad debts being collected by member. The purpose of this research is to find out the factors that cause uncollectible accounts in the West Sumatra INKINDO organization. The type of data used in this study is primary data. The data collection technique used was document data collection and questionnaire distribution to members of INKINDO West Sumatra. The data analysis method used is data reduction, data presentation and drawing conclusions. The results of this study indicate that the factors causing the emergence of uncollectible accounts among members of INKINDO West Sumatra are the uneven distribution of packages obtained by members, the absence of recapitulation of member receivables each year, the nominal amount of membership dues each year, fines for not participating in organizational activities which are quite large and income imbalance and operating expenses that must be borne by members.